Differences in Risk Factors for Metabolic Syndrome and Stress Levels between School Teachers Living in Rural and Urban Areas in Karawang, Indonesia during the COVID- 19 Pandemic - Bhagya, Kalani; Fikri, Al Mukhlas; Elvandari , Milliyantri (Jurnal Gizi dan Pangan, 2023)
This study investigated the differences in metabolic syndrome risk factors and psychological stress levels among school teachers in rural and urban areas during the COVID-19 pandemic in Indonesia. Waist circumference, High-Density Lipoprotein (HDL) and triglyceride levels, hypertension status, and fasting blood glucose were measured in 71 participants. The results showed higher rates of large waist circumference and hypertension in rural areas, and higher rates of low HDL, high triglyceride, and high fasting blood glucose in urban areas. In addition, a greater percentage of individuals in both rural and urban areas experienced high level of stress. These findings suggest different health risks associated with living in different areas during the pandemic.